Digital divide: facilitating conditions and usage of Google Classroom for teachers in rural and urban secondary schools in Malaysia - Yap, Phoebe Soong Yee; Moses, Priscilla; Cheah, Phaik Kin; Md. Khambari, Mas Nida; Wong, Su Luan; Yu, Fu-Yun (Universiti Pendidikan Sultan Idris, 2024)
Online teaching and learning have caused many students and teachers with unprecedented challenges leading to a phenomenon known as the digital divide, which is the disparity between individuals who have access to Information and Communication Technologies (ICT) and those who do not. Therefore, this study aims to investigate the significant difference in facilitating conditions (network connection, technical issues, school infrastructure) and usage of Google Classroom for teachers in rural and urban teachers. In this study, 395 responses were collected from secondary school teachers through an online survey, that included demographic information and 22 survey items. Descriptive statistics and t-test analysis were used to analyze the data. Findings found that there are significant differences in technical issues and usage of Google Classroom for teachers in rural and urban schools. This research offers valuable insights for educational stakeholders especially the schools and government to provide tailored technical support and ongoing training to the teachers in Malaysia, especially those in rural areas. By strategically allocating educational resources and executing policies that cater to the varying needs of these different environments, it is believed that policymakers and educational stakeholders can bridge the digital divide and create educational equity nationwide.